Joking Hadith Contextualization to Prank Phenomenon in the Contemporary Era (Application Study Hassan Hanafi's Hermeneutics) - Labib, Muhammad Alfreda Daib Insan; Syamsul, Ilham; Priyatmaja, Ahmad Amiruddin; Bintara, Anggi Radar; Muzammil, Shofiyullah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This article discuss about application theory Hassan Hanafi's hermeneutics in dissect phenomenon rampant pranks taking place in the contemporary era. In the discussion, researcher will do analysis based hadith prophet. Research methods This is qualitative. Whereas processing the data use method descriptive analytical. In the article This is the problem under study among them is background behind along with steps Hassan Hanafi's hermeneutics, postulates based on the Koran and hadith which have correlation with discussion this, and application Hassan Hanafi's hermeneutics towards hadith that has suitability with phenomenon prank. Study results show that 1). Steps Hassan Hanafi's hermeneutics is critics history, eidetic, and praxis. 2). At least there is three verse that has linkages with pranks, that is Al-Hujurat Verse 11, Al-A'raf Verse 51, Ash-Shura Verse 42. Whereas editorial hadith that has linkages with pranks, that is Musnad Ahmad 8366, Sunan Abu Dawud 4350, Sunan Abu Dawud 4351. 3). Phenomenon prank punished as something that is permissible, except There is detrimental elements, then matter the will change law pranks become haram.